Efficacy of Betaproteobacteria-based insecticides for managing whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae), on cucumber plants - Shannag Hail Kamel (Open Agriculture)
The whitefly, B. tabaci, poses a significant threat to cucumber cultivation. While traditional insecticides are commonly used to manage this pest, they frequently raise ecological and health concerns. In contrast, naturally derived biopesticides offer a promising and environmentally friendly alternative for controlling whitefly populations, thereby reducing negative impacts on non-target organisms. This study evaluates the efficacy of two novel Betaproteobacteria-based insecticides: Burkholderia spp. strain A396 (Venerate XC) and Chromobacterium subtsugae strain PRAA4-1 (Grandevo WDG) against B. tabaci. Leaf-dipping bioassays were performed to compare the effectiveness of these biopesticides with spirotetramat (Movento® 240 SC) as a standard control. Both biopesticides significantly reduced egg hatching rates and decreased survival rates in nymphs and adults by 74.5, 94.8, and 76.5%, respectively, indicating concentration-dependent effects. Direct exposure to Venerate and Grandevo exhibited toxicity levels comparable to spirotetramat across all tested concentrations. However, spirotetramat residues were found to be more toxic to adult whiteflies than the other products, while the mortality associated with Venerate residues was relatively low. Both Venerate and spirotetramat produced significant sublethal effects on the duration of nymph development, although these effects were not consistently concentration-dependent; Grandevo did not affect nymph development. These findings suggest that the novel insecticides may effectively manage B. tabaci populations in Jordan, warranting further investigation under field conditions.